2013
DOI: 10.2174/1874325001307010219
|View full text |Cite
|
Sign up to set email alerts
|

Management of Infection After Intramedullary Nailing of Long Bone Fractures: Treatment Protocols and Outcomes

Abstract: Implant related sepsis is a relatively unusual complication of intra-medullary nail fixation of long bone fractures. Depending on the extent of infection, timing of diagnosis and progress of fracture union, different treatment strategies have been developed. The aim of this review article is to collect and analyze the existing evidence about the incidence and management of infection following IM nailing of long bone fractures and to recommend treatment algorithms that could be valuable in everyday clinical pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
(119 reference statements)
1
50
0
Order By: Relevance
“…Clinically, the development of infection after intramedullary nailing may progress as far as sepsis. Even in the event of sepsis, it has been reported that union can still occur in a fracture that has stable fixation with intramedullary nailing [16]. In the current study, a high number of S aureus (1 9 10 8 ) was used to create a local infection rate of 100% with low morbidity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Clinically, the development of infection after intramedullary nailing may progress as far as sepsis. Even in the event of sepsis, it has been reported that union can still occur in a fracture that has stable fixation with intramedullary nailing [16]. In the current study, a high number of S aureus (1 9 10 8 ) was used to create a local infection rate of 100% with low morbidity.…”
Section: Discussionmentioning
confidence: 78%
“…Torque to failure and stiffness both were lower in the infection group than in the control group at 6 weeks, but with the numbers available for testing, they were not different at 3 weeks (p = 0.615 and p = 1, respectively; Table 2 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]; p = 0.004) both were greater in the control group than in the group with infection. Maximum torque to failure was lower in the infection group than in the control group at all time points.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Advanced age has been shown to be a risk factor for postoperative complications such as nonunion as well as a risk factor for developing a long bone fracture. 5,8,9,27 ASA score was significantly predictive of postoperative complications, in which each unit increase was associated with a 2-fold increase in developing a postoperative complication. Knowing the risk factors for postoperative complications of lower extremity long bone fractures, surgeons will be able to better risk stratify patients based on fracture type and be able to better prevent acute postoperative complications.…”
Section: Discussionmentioning
confidence: 93%
“…[4][5][6][7] Older individuals also face an increased risk of long-bone fractures due to a decrease in bone density associated with age and increased risk of falling. 5,8,9 Management of long bone fractures varies from conservative methods including casting and bracing to surgical, encompassing open reduction internal fixation (ORIF) with plates or intramedullary nailing (IMN). 2,3 Optimal treatment for long-bone fractures is still debated among orthopaedic surgeons and depends on various factors.…”
Section: Introductionmentioning
confidence: 99%